Sosialisasi Pengetahuan dan Keterampilan Mediasi Desa Wisata pada Mahasiswa Sekolah Tinggi Pariwisata Mataram - Uwi Martayadi; Dyah Indraswati; Lalu M. Iswadi Athar; Luh Widiani; Lalu Mahsar (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
The purpose of Community Service (PKM) is to foster student awareness, promote peaceful conflict resolution, impart mediation skills, enhance problem-solving abilities, and instill ethical values associated with mediation. PKM is conducted through interactive socialization sessions that incorporate lectures and question-and-answer formats. The desired outcome of PKM activities is to equip students with knowledge and proficiency in mediation, thereby empowering them to contribute positively to their communities. Through PKM, students gain an understanding of what mediation entails, discover the presence of mediation institutions within each Regency/City in Lombok, grasp the importance of the mediator code of ethics, and familiarize themselves with mediation regulations. By providing new knowledge and skills, Sekolah Tinggi Pariwisata Mataram aims to convey the message that issues or conflicts faced by tourism villages can be effectively resolved through mediation, obviating the need for legal recourse.